Driving Hierarchical Collagen Fiber Formation for Functional Tendon, Ligament, and Meniscus Replacement. (February 2021) - Puetzer, Jennifer L.; Ma, Tianchi; Sallent, Ignacio; Gelmi, Amy; Stevens, Molly M.
Abstract: Hierarchical collagen fibers are the primary source of strength in musculoskeletal tendons, ligaments, and menisci. It has remained a challenge to develop these large fibers in engineered replacements or in vivo after injury. The objective of this study was to investigate the ability of restrained cell-seeded high density collagen gels to drive hierarchical fiber formation for multiple musculoskeletal tissues. We found boundary conditions applied to high density collagen gels were capable of driving tenocytes, ligament fibroblasts, and meniscal fibrochondrocytes to develop native-sized hierarchical collagen fibers 20–40 μm in diameter. The fibers organize similar to bovine juvenile collagen with native fibril banding patterns and hierarchical fiber bundles 50–350 μm in diameter by 6 weeks. Mirroring fiber organization, tensile properties of restrained samples improved significantly with time, reaching 1 MPa. Additionally, tendon, ligament, and meniscal cells produced significantly different sized fibers, different degrees of crimp, and different GAG concentrations, which corresponded with respective juvenile tissue. To our knowledge, these are some of the largest, most organized fibers produced to date in vitro . Further, cells produced tissue specific hierarchical fibers, suggesting this system is a promising tool to better understand cellular regulation of fiber formation to better stimulate it in vivo after injury. Graphical abstract: Image 1